Comparison of automated and manual viral nucleic acid extraction kits for Covid-19 detection using qRT-PCR - Joseph, Narcisse; Bahtiar, Norliza; Mahmud, Farhatani; Abdul Hamid, Kamsiah; Raman, Ragenee; Hui, Yee Chee; Amin Nordin, Syafinaz (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: The emergence of a novel Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has resulted in a pandemic. Rapid and accurate diagnosis method is crucial to reduce the disease burden and to improve early diagnosis approaches to control of the disease. Real time Reverse transcriptase PCR (qRT-PCR) has been identified by the World Health Organization as the most sensitive and specific method of detection. However, the success of this assay relies on the quantity and quality of the extracted viral RNA. Methods: Various methods have been developed for nucleic acid extraction however, the methods have not been assessed. RNA extraction was performed from 24 nasopharyngeal swab samples using a manual extraction kit (GF-1) and an automated extraction kit (Genolution). The concentration and purity of the extracted RNA samples were measured, and its performance were tested using qRT-PCR. Results: The average concentration and purity of the RNA samples extracted using GF-1 kit was higher compared to Genolution. Similarly, the qRT-PCR assay using the RNA samples extracted using manual extraction was better compared to automated kit. Conclusion: Both the manual and automated extraction kits have its advantages and disadvantages in terms of yield and purity. However, with proper optimization, both methods may be used for routine molecular diagnostic of COVID-19 in laboratories.